Relationship between competitive anxiety and resilience in high-performance water sports practitioners during COVID-19 - Córdova-Castillo, Rodrigo (2023)
The aim was to determine if there is a relationship between competitive anxiety and resilience in Peruvian high-performance water sports practitioners during COVID-19 confinement. The sample was made up of 84 athletes of both sexes (42 men and 42 women), between 18 and 43 years old, with an average age of 22.94. The type of sampling was non-probabilistic and intentional. The SAS-2 and ERCD instruments were used. The main results show that women have more Total Competitive Anxiety and Worries than men, while men obtain greater Total Resilience, Personal Competence and Self-Acceptance than women. Furthermore, Total Competitive Anxiety is negatively related to Total Resilience. It is concluded that resilience plays an important role in reducing competitive anxiety, which in turn is related to better performance and well-being in high-performance athletes. In addition, it is essential to pay attention to gender differences, since women may require greater training in resilience, stress-coping skills, and emotional management.